Polyphosphate Accumulation Tracks Incremental P-Enrichment in a Temperate Watershed (Pennsylvania, United States) as an Indicator of Stream Ecosystem Legacy P - Taylor, Shayna; Saia, Sheila M.; Buda, Anthony R.; Regan, John M.; Walter, M. Todd; Carrick, Hunter J. (Frontiers in Environmental Science, 2022)
Legacy P concentrations resulting from historic additions of phosphorus (P) to the landscape may impede rapid remediation of P pollution and achievement of water quality management goals. Herein, we hypothesized that the capacity of stream biofilms to assimilate new polyphosphate is will the degree of stream legacy phosphorus (P). To test this hypothesis, we deployed a series of in situ enrichment experiments were deployed at five sites of varying land cover in central Pennsylvania, USA. Incremental P-loading was delivered using vials fitted with porous lids, that contained agar enriched with 6 levels of P (as DIP, dissolved inorganic P) loading with rates ranging from 0 to 1,540 µg PO4-3/day; these loading rates mimicked natural stream P loadings. Substrata were incubated at stream sites for a relatively short incubation period (12 days), to measure uptake rates; after which, biofilms growing on the lids were removed and their tissue content was analyzed for biomass (as chlorophyll) and various forms of particulate phosphorus. Polyphosphate (polyP) accumulated by stream biofilms at all sites closely tracked the release of dissolved inorganic P from experimental enrichment assays. Comparatively, biofilms accumulated a relatively little amounts of PIP (Particulate inorganic P) and other forms of organic P (e.g., DNA, RNA, lipids, proteins). Viewed at the watershed scale, land use appeared to affect P accumulation, where sites dominated by forest cover had a higher capacity for P storage, while sites dominated by agriculture did not; this underscores the importance of polyP storage as an indicator of legacy P pollution.